BUMDes Policy in Supporting Village Economic Independence Through the development of the Sambibulu Tourism Village at Sidoarjo - Yandika Sandah; Hendra Sukmana (Universitas Muhammadiyah Gorontalo, 2022)
This study aims to analyze the implementation of the Sambimadu BUMDes Policy in supporting village economic independence through the development of Tourism Villages. This research method is descriptive qualitative. The type of data used in this research is qualitative data, which is divided into primary data and secondary data. Implementing BUMDes policies in the development of Tourism Villages is the focus of this research. Sources of data obtained through Library Research are available online and offline, such as scientific journals, books, and news from trusted sources. The results showed that the implementation of the BUMDes policy in supporting the village's economic independence through the development of the Sambibulu Tourism Village had not been fully successful, this was due to the incompetent Human Resources of the Sambimadu BUMDes. The characteristics shown by BUMDes staff are that they only prioritize their interests so that they underestimate their duties and responsibilities. And they do not fully understand the BUMDes policy in developing tourist villages regarding their cognitive abilities. On the one hand, there is good communication support between the Village Government and BUMDes Sambimadu because every week, it evaluates activities to correct deficiencies in the BUMDes Policy Implementation process.